2019
DOI: 10.1002/mbo3.913
|View full text |Cite
|
Sign up to set email alerts
|

Production of single cell protein from manure as animal feed by using photosynthetic bacteria

Abstract: To reduce the cost of protein feedstock for animal feed, the use of single cell protein (SCP) produced from waste of animal agriculture is an interesting choice. This study reveals that chicken manure was the best substrate for SCP production by submerged fermentation using photosynthetic bacteria compared to swine, cow, and buffalo manure. Regression analysis showed that the productions were found to be significantly influenced by chicken manure content, inoculum size, and cultivation time. Response surface m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…The report of Hongpattarakere and H-Kittikun (1995) indicated that increasing inoculum size above 5% has no effects on the protein content of Schwunniomyces castellii B5285 biomass grown in cassava starch. Patthawaro and Saejung (2019) also reported no significant difference in the Rhodopseudomonas faecalis biomass produced at 20 and 30% inoculum levels. Yunus et al (2015) reported maximum protein yield in Candida utilis and Rhizopus oligosporus biomass grown in wheat bran at 10% (v/w) inoculum size using 48 hours old culture.…”
Section: Inoculation and Incubationmentioning
confidence: 92%
“…The report of Hongpattarakere and H-Kittikun (1995) indicated that increasing inoculum size above 5% has no effects on the protein content of Schwunniomyces castellii B5285 biomass grown in cassava starch. Patthawaro and Saejung (2019) also reported no significant difference in the Rhodopseudomonas faecalis biomass produced at 20 and 30% inoculum levels. Yunus et al (2015) reported maximum protein yield in Candida utilis and Rhizopus oligosporus biomass grown in wheat bran at 10% (v/w) inoculum size using 48 hours old culture.…”
Section: Inoculation and Incubationmentioning
confidence: 92%
“…Some involve processing manure into a more concentrated dry or liquid fertilizer, although economical efforts to do so today require a high price for organic fertilizer. Some technologies would use manure as a source of protein for animal feed by feeding the manure either to insects or single-celled organisms, such as bacteria (Patthawaro and Saejung 2019;Roffeis et al 2015). None of these ideas today would be cheap enough for implementation, but they are worth continued exploration.…”
Section: G More Innovative Manure Management Optionsmentioning
confidence: 99%
“…Upcycling of nutrients from animal manure into SCPs using photosynthetic bacteria is an attractive option for recovering valuable nutrients (Patthawaro & Saejung, 2019), but animal manure can be a source of bacteria and viruses. There is also increasing interest in using bioactive peptides derived from animal by-products (e.g., porcine intestine, porcine mucosa, salmon viscera, or poultry tissues hydrolysates) and soybean protein isolates to improve growth performance and health of weaned pigs, young calves, poultry, and fish diets (Hou et al, 2017).…”
Section: Biosafety Of Emerging Feed Additives and Ingredientsmentioning
confidence: 99%